2022
DOI: 10.3390/ijms232012691
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Increases Podocyte Survival and Autophagic Flux after Adriamycin-Induced Injury

Abstract: The kidney glomerular filtration barrier (GFB) is enriched with heparan sulfate (HS) proteoglycans, which contribute to its permselectivity. The endoglycosidase heparanase cleaves HS and hence appears to be involved in the pathogenesis of kidney injury and glomerulonephritis. We have recently reported, nonetheless, that heparanase overexpression preserved glomerular structure and kidney function in an experimental model of Adriamycin-induced nephropathy. To elucidate mechanisms underlying heparanase function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Indeed, overexpression of HPSE was associated with a significant transcriptional upregulation of autophagy genes BCEN1, ATG5, and ATG12. Nevertheless, the autophagy flux was increased in H podocytes, which was reversed by HPSE inhibitor, SST0001 (Abu‐Tayeh Suleiman et al, 2022). Indeed, Yang et al also demonstrated that active HPSE and inactive HPSE mutant proteins promoted the gastric cancer growth, which in part due to activated TFEB‐mediated autophagy.…”
Section: The Protumorigenic Role Of Hpse In Cancer Progressionmentioning
confidence: 99%
“…Indeed, overexpression of HPSE was associated with a significant transcriptional upregulation of autophagy genes BCEN1, ATG5, and ATG12. Nevertheless, the autophagy flux was increased in H podocytes, which was reversed by HPSE inhibitor, SST0001 (Abu‐Tayeh Suleiman et al, 2022). Indeed, Yang et al also demonstrated that active HPSE and inactive HPSE mutant proteins promoted the gastric cancer growth, which in part due to activated TFEB‐mediated autophagy.…”
Section: The Protumorigenic Role Of Hpse In Cancer Progressionmentioning
confidence: 99%